Unraveling the uncommon: Pneumoperitoneum induced by emphysematous pyelonephritis - Oumaima Mesbah, MD; Badr Kabila, MD; Basma Beqqali, MD; Omar El Aoufir, PhD; Laila Jroundi, PhD (Radiology Case Reports)
Emphysematous pyelonephritis is a necrotizing infection of the renal parenchyma by gas-forming organisms, with a risk of the gas extending into peri-nephric or para-renal spaces and in advanced cases, the involvement may be extensive and bilateral. It is a common complication in patients with long-term diabetes, primarily caused by Gram-negative organisms or, in some cases, anaerobes. The diagnosis of emphysematous pyelonephritis is made by clinical features and confirmed by computed tomography. Treatment is decided based on the computed tomography classification, with minimally invasive conservative techniques and antibiotic treatment before considering nephrectomy. We present a case of a 30-year-old women with an emphysematous pyelonephritis associated with pneumoperitonuem.